Business cycle dynamics in the CEE countries: a political economy approach - Müge Adalet; Sumru Öz (TÜSİAD-Koç University Economic Research Forum, 2010)
This paper uses a simple VAR analysis to examine 5 CEE countries (the Czech Republic, Hungary, Poland, Romania and Slovakia) in order to understand whether their business cycles are synchronized with each other and/or with the major economies that they are supposed to be linked with, namely the US, Germany and Russia. We find that there are differences across the CEE countries themselves and that there is no common CEE business cycle. Comparing the individual CEE business cycles with those of the dominant economies, we find that Hungary and Poland are related to the US business cycle, reflecting the fact that they are more integrated with the global economy, whereas Slovakia is closer to the Russian cycle. Finally, splitting the sample into the late 1990s and 2000s due to the transition nature of these economies in the former period shows that the influence of Russia on the CEE economies has declined over time. However, in contrast to the expectations that CEE countries are likely to be affected by Germany in the second half of the sample due to EU negotiations followed by full membership, among the CEE countries only the business cycle of Slovakia is synchronized with that of Germany. On the other hand the Czech Republic, Hungary and Poland are synchronized with the US business cycle, showing that globalization has decreased the importance of distance.
Keywords: E32; F15; F41; 330; business cycle synchronization; CEE countries; EMU; Konjunkturzusammenhang; Tschechische Republik; Ungarn; Polen; Rumänien; Slowakei